$\begin{array}{1 1}(A)\;\sqrt 1 : \sqrt 2 : \sqrt 3: \sqrt 4\\(B)\;1:1:1:1 \\(C)\;(\sqrt 1-0) :(\sqrt 2-\sqrt1) :(\sqrt 3 -\sqrt 3).... \\(D)\;\frac{1}{\sqrt 1}:\frac{1}{\sqrt 2} :\frac{1}{\sqrt 3} :\frac{1}{\sqrt 4}\end{array} $

Want to ask us a question? Click here

Browse Questions

Ad |

0 votes

0 votes

$1= \large\frac{1}{2} $$gt_1^2 => t_1 = \bigg(\sqrt{ \large\frac{2}{g}}\bigg)$

$2= \large\frac{1}{2} $$g(t_1+t_2)^2 => t_1+t_2 = \bigg(\sqrt{ \large\frac{2}{g}}\bigg)$$\sqrt 2$

$2= \large\frac{1}{2}$$g (t_1+t_2+t_3)^2 => t_1+t_2+t_3=\bigg(\sqrt{ \large\frac{2}{g}}\bigg) $$ \sqrt 3$

$t_1 :t_2:t_3=\sqrt 1 : (\sqrt 2 -\sqrt 1 ): (\sqrt 3 - \sqrt 2)$

Hence C is the correct answer.

Ask Question

Take Test

x

JEE MAIN, CBSE, NEET Mobile and Tablet App

The ultimate mobile app to help you crack your examinations

...